Environmentally friendly processed fibre product & method of making the same. - Halis, Rasmina; Mohd Salleh, Naimah; Konami, Yasuo (2011)
The present invention provides a useful processed fibre composition comprising a plurality of fibres derived from a tropical plant, in which the plurality of fibres having a cellulose content of more than 60 wt% and a lignin content of less than 10 wt%. The plurality of fibres is derived from a tropical plant that includes banana.